Psychological distress in hypertension: Prevalence and links to self-care in Gonabad, Iran - Fatemehzahra Naddafi; Alireza Jafari; Mahbobeh Nejatian; Hadi Tehrani (PLoS ONE, 2026)
Introduction A critical component in the hypertension management and the prevention of its life-threatening complications, is self-care. Psychological factors such as stress, anxiety and depression may significantly influence self-care behaviors in people with hypertension. Therefore, this study aimed to investigate the prevalence of anxiety, depression and stress and their association with self-care levels among hypertensive patients. Methods This analytical cross-sectional study was conducted in 2024−2025 in Gonabad, Iran, among a population of 509 hypertensive patients. Participants were selected through cluster random sampling, with inclusion criteria consisting of: A confirmed diagnosis of hypertension by a physician, Willingness to provide informed consent, Absence of cognitive impairment, and At least one year of residency in Gonabad. Data were gathered by three self-administered questionnaires: a demographic questionnaire, the DASS-21 (Depression, Anxiety, and Stress Scale), and the Self-Care of Hypertension Inventory (SC-HI V 3 ). The collected data were analyzed using SPSS v25, with statistical tests including independent t-tests, ANOVA, Multiple Linear Regression and Pearson’s correlation. Results The majority of participants in this study were female and older persons (age > 60 years). Marital status showed a significant association with levels of depression, anxiety, and stress. Additionally, variables such as age group, marital status, education level, and occupation were significantly correlated with hypertension self-care levels and all three of its subscales. Furthermore, 62.5%, 75.2%, and 59.3% of hypertensive patients exhibited depression, anxiety, and stress, respectively. Pearson’s correlation analysis revealed a significant negative association between: Depression and self-care (r = −0.314, p < 0.001), Anxiety and self-care (r = −0.330, p < 0.001). A significant negative correlation was also observed between depression/anxiety and the age at hypertension onset. Variables of Depression, Anxiety, Stress, Age, Education and Income could predict 15% of self-care of hypertension variance. Conclusion The prevalence of psychological disorders—particularly stress, depression, and anxiety—among hypertensive patients is alarmingly high. Moreover, significant negative correlations exist between these mental health conditions and hypertension self-care levels. These findings underscore the critical need for: Preventive interventions and Mental health promotion programs tailored to this population. Policymakers, healthcare providers, and researchers must prioritize integrating psychological support into hypertension management strategies to mitigate these adverse effects and improve patient outcomes.